Decision aids for shared decision-making in uro-oncology: a systematic review : review : education - Grüne, Britta; Kriegmair, Maximilian; Lenhart, Maximilian; Michel, Maurice Stephan; Huber, Johannes; Köther, Anja K.; Büdenbender, Björn; Alpers, Georg W. (European urology focus, 2022)
Context - Decision aids (DAs) aim to support patients in the process of shared decision-making for complex treatment decisions. To improve patient-centered care in uro-oncology, it is essential to evaluate the availability and quality of existing DAs. - Objective - To assess the quality of existing DAs for patients across the most prevalent uro-oncological entities. - Evidence acquisition - This study was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) guidelines. A systematic literature search (MedLine, Cochrane Library, Web of Science Core Collection, and CCMed) was conducted to identify DAs for treatment decisions for patients with prostate, renal, or bladder cancer. All studies reporting on the development or evaluation of DAs were included. The DAs were examined based on the International Patient Decision Aid Standards (IPDAS) and the evaluation studies were compared in accordance with Standards for Universal reporting of a patient Decision Aid Evaluations (SUNDAE). - Evidence synthesis - The literature search identified 1995 potentially relevant publications. Thirty-two studies reporting on 25 DAs met the inclusion criteria. Twenty-two DAs address prostate cancer, two renal tumor, and one bladder cancer. In the majority of DAs (n = 20), patients can enter individual data. A few (n = 6) DAs allow for personalization using a risk-adapted presentation of treatment options. The percentage of IPDAS criteria met in DAs ranged between 50% and 100% (median 87.5%), and the studies’ adherence to the SUNDAE checklist was between 62% and 96% (median 86.6%). Evaluation studies suggest that interventions are likely efficacious. However, a preliminary meta-analysis revealed no significant difference between "DA" and "usual care" for decisional conflict or decisional regret. - Conclusions - This review highlights that a number of well-developed DAs exist in urology. However, there is a need for specific instruments targeting kidney and bladder cancer. Personalization of tools and adherence to international standards of DAs should be further improved. - Patient summary - The majority of uro-oncological decision aids target prostate cancer, whereas fewer address kidney or bladder cancer. The quality of the existing instruments is high, but can be increased further to better address specific needs of individual patients.
Online verfügbar: 10. Mai 2021, Artikelversion: 26 August 2022
Gesehen am 20.02.2024